Difference between Sports and Hobbies - Arop, Arop Deng Kuol (European Journal of Information and Knowledge Management, 2023)
Purpose: The purpose of this research was to produce a work that will resolve the problem of neglecting the importance of sports and hobbies vocabulary in our national educational system in South Sudan. It will also work as a catalase of change in the Southern Sudanese system of academic development. Methodology: A desktop literature review was used for this purpose. The study's relevant seminal references and journal articles were identified using Google Scholar and other database engines. Findings: The findings revealed that the main problem in learning English in South Sudan is the curriculum's lack of English vocabulary related to Sports and Hobbies. And this results negatively in a flawed educational system in which school leavers are graduated from their schools with little knowledge, if not ignorant, because sports and hobbies knowledge is totally or entirely ignored in setting our curriculum. Unique Contribution to Theory, Policy, and Practice: The new idea in this study is to give importance to vocabulary related to sports and hobbies as the shortest way to help learners and indicate the necessity of sports and hobbies to be part of our culture and to pave the road for their existence as part of our national phenomenon. Besides, it will significantly contribute to the actual knowledge of the academic community's current understanding of their subject. Moreover, this research will challenge other research on learning English as a Foreign Language in South Sudan because it looks deeply at the root of this problem. This poorly planned educational system never gives room for new ideas to develop. Besides, this proposal will also provide a solution for ignoring sports and hobbies vocabularies in our educational system and will help inject English vocabulary into our curriculum development. Being the first in South Sudan, this research will significantly help teachers, students, the Ministry of Education, at home, and whoever wants to learn vocabulary related to sports and hobbies. It will also be helpful and reachable for many people learning English as a foreign language. It will also help provide English vocabulary related to sports and hobbies through research in our educational system.